2020
DOI: 10.1021/acs.jpcc.9b11609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymer Morphology on Dilute Donor Organic Solar Cells

Abstract: Dilute donor organic solar cells (OSCs) aim to circumvent the trade-off between open-circuit voltage V oc and short-circuit current density j sc by decreasing the donor/acceptor interface. The main challenge of such an architecture is to realize hole extraction pathways. Due to the reduced donor content, there are negligible percolation paths toward the contacts for the photogenerated holes. Hole transport toward the contacts can either happen by tunneling between the diluted polymers, hole backtransfer to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Recently, there has been significant interest in understanding how holes are transported to the anode in fullerene-based OPVs. Several groups propose that holes can be transported through the aggregation of donor molecules , and donor polymer networks, which form a percolating path to the anode. Our results show evidence of P3HT accumulation on the top surface in both conventional and inverted architectures, so it is possible that P3HT molecules could form percolating pathways to the top anode contact in the inverted architecture for efficient hole extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been significant interest in understanding how holes are transported to the anode in fullerene-based OPVs. Several groups propose that holes can be transported through the aggregation of donor molecules , and donor polymer networks, which form a percolating path to the anode. Our results show evidence of P3HT accumulation on the top surface in both conventional and inverted architectures, so it is possible that P3HT molecules could form percolating pathways to the top anode contact in the inverted architecture for efficient hole extraction.…”
Section: Discussionmentioning
confidence: 99%
“…All calculations were performed using our kMC model, which has been used successfully to analyze the role of permittivity and energetics on the charge separation efficiency and dynamics, tuning the exciton dynamics using phosphorescent sensitizers, the role of interface energetics on the open-circuit voltage, and the origin of charge transport and the importance of the morphology in dilute donor organic solar cells. ,, Here, we briefly summarize the rate models used in the kMC simulations and the system setup. Details on the Monte Carlo algorithm based on the Gillespie method can be found elsewhere. , …”
Section: Methodsmentioning
confidence: 99%
“…Second, the dilute donor approach has been employed by several groups to improve as a platform for increasing the AVT while maintaining a high PCE due to increased IR absorption by a narrow band gap acceptor compound and reduced absorption by a donor compound that absorbs (partially) in the visible range [80,[111][112][113]. In 2021, Yao et al studied PM6:Y6 OPVs with reduced donor content and found an efficiency of over 10% in dilute donor solar cells with only 10 wt% PM6, thanks to efficient charge generation, electron and hole transport, slow charge recombination, and field-insensitive extraction [111].…”
Section: Current Performance and Strategies To Increase Luementioning
confidence: 99%
“…Highly diluted polymer donor chains may not form a percolating network for charge extraction, in contrast to the common morphological picture for BHJ solar cells. Theoretical and experimental work aims to explain successful photocurrent generation in such highly diluted donor (fullerene) OPVs with isolated donor molecules by a hole back-transfer mechanism that is dependent on the HOMO-HOMO offset between donor and acceptor [113,116,117].…”
Section: Current Performance and Strategies To Increase Luementioning
confidence: 99%